The black swan : the impact of the highly improbable - Taleb, Nassim Nicholas, 1960- (New York : Random House Trade Paperbacks, 2010)
Examines the role of the unexpected, discussing why improbable events are not anticipated or understood properly, and how humans rationalize the black swan phenomenon to make it appear less random.
Prologue -- Umberto Eco's antilibrary, or how we seek validation. The apprenticeship of an empirical skeptic ; Yevgenia's black swan ; The speculator and the prostitute ; One thousand and one days, or how not to be a sucker ; Confirmation shmonfirmation! ; The narrative fallacy ; Living in the antechamber of hope ; Giacomo Casanova's unfailing luck : the problem of silent evidence ; The Ludic fallacy, or the uncertainty of the nerd -- We just can't predict. The scandal of prediction ; How to look for bird poop ; Epistemocracy, a dream ; Appelles the Painter, or what do you do if you cannot predict? -- Those gray swans of Extremistan. From Mediocristan to Extremistan and back ; The bell curve, that great intellectual fraud ; The aesthetics of randomness ; Locke's madmen, or bell curves in the wrong places ; The uncertainty of the phony -- The end. Half and half, or how to get even with the black swan -- Epilogue : Yevgenia's white swans -- Postscript essay: on robustness an fragility, deeper philosophical and empirical reflections. Learning from mother nature, the oldest and the wisest ; Why I do all this walking, or how systems become fragile ; Margaritas ante porcos ; Asperger and the ontological black swan ; (Perhaps) the most useful problem in the history of modern philosophy ; Fourth quadrant, the solution to that most useful of problems ; What to do with the fourth quadrant ; Ten principles for a black-swan-robust society ; Amor fati: how to become indestructible.
"Originally published in hardcover and in slightly different form in the United States ... by Random House in 2007."-T.p. verso.
Includes bibliographical references (pages [401]-429) and index.
BBS
Keywords: Uncertainty (Information theory) -- Social aspects; Corporate Finance; Forecasting